Case Analysis of the Social Skills of Children with Autism in the Inclusion Program - Silin, Merriam S. (International Journal of Psychosocial Rehabilitation, 2020)
Inclusion is an instructional program of the Department of Education which caters to learners with various exceptionalities in a regular education classroom. As enrollees with certain exceptionalities arises in public schools in the Philippines, it has become essential to look critically on the effects of inclusion to social skills of children with special needs particularly to children with autism (CWAs). Autism is a developmental disorder characterized by impairment in social interaction, communication and behavior. A qualitative case study design was used which involves observation, in-depth individual interview, and biographical methods such as life history, narratives, records, and analysis of documents. Accordingly, CWAs are able to cooperate during class, interact in social activities and gatherings, join group/peer work and activities, comply with the teacher and classmates’ requests, help other students, listen attentively to their classmates and to the teacher although there are times wherein they wait for others to talk to them which were not evident in the past. Because of these results, it is recommended that the school should develop a more comprehensive and attainable inclusive program philosophy, goals, vision and mission to ensure quality inclusion program for children with autism in the regular classroom.